2016
DOI: 10.1016/j.arthro.2016.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Commentary: Anterior Cruciate Ligament Injury and Our National Pastime

Abstract: Baseball players are most likely to incur an anterior cruciate ligament injury while fielding or base running. Infielders and outfielders are most at risk, followed by pitchers. Return to play at the preinjury level after anterior cruciate ligament reconstruction is highly likely for these athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…ACLR has become the gold standard treatment for ACL tears in athletes who wish to return to sport at a high level. 8,13 The RTS rate in this study was 80%, which is consistent with a prior study by Mai et al 24 that reported an RTS rate of 80% for MLB players undergoing ACLR. The study by Mai et al reported an RTS rate of 95.8% in National Hockey League (NHL), 82.4% in National Basketball Association (NBA), and 85.5% in National Football League (NFL) athletes after ACLR.…”
Section: Discussionsupporting
confidence: 91%
“…ACLR has become the gold standard treatment for ACL tears in athletes who wish to return to sport at a high level. 8,13 The RTS rate in this study was 80%, which is consistent with a prior study by Mai et al 24 that reported an RTS rate of 80% for MLB players undergoing ACLR. The study by Mai et al reported an RTS rate of 95.8% in National Hockey League (NHL), 82.4% in National Basketball Association (NBA), and 85.5% in National Football League (NFL) athletes after ACLR.…”
Section: Discussionsupporting
confidence: 91%